1989
DOI: 10.1111/j.1600-0447.1989.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of suicide risk by computer‐delivered self‐rating questionnaire: preliminary findings

Abstract: A prospective study of 167 consecutive patients admitted to a general hospital following an episode of deliberate self-harm was carried out; 102 patients were interviewed by computer and then by a psychiatrist who was blind to the results of the computer interview. The computer interview consisted of a self-rating modification of the Hamilton Rating Scale for Depression and a novel questionnaire developed to assess suicidal ideation. This article explores the preliminary findings in these patients and suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 12 publications
(9 reference statements)
1
53
0
1
Order By: Relevance
“…Subjects in out-patient clinical trials may well deny stigmatized suicidal ideas and behaviors causing Type II error (false negatives). This difference between clinician and self-report assessments regarding suicidality has been found across many years with higher levels of false negatives in clinician ratings than in self-report assessments (Greist et al, 1973;Levine et al, 1989;Vitiello et al, 2009). Clinician raters in clinical trials may also be biased against finding suicidality if suicidality is an exclusion criterion for participation in a clinical trial.…”
Section: Tablementioning
confidence: 99%
“…Subjects in out-patient clinical trials may well deny stigmatized suicidal ideas and behaviors causing Type II error (false negatives). This difference between clinician and self-report assessments regarding suicidality has been found across many years with higher levels of false negatives in clinician ratings than in self-report assessments (Greist et al, 1973;Levine et al, 1989;Vitiello et al, 2009). Clinician raters in clinical trials may also be biased against finding suicidality if suicidality is an exclusion criterion for participation in a clinical trial.…”
Section: Tablementioning
confidence: 99%
“…There is evidence that increased self-disclosure may be found with stand-alone computerized tests (e.g., Levine, Ancill, & Roberts, 1988), although the effect may be mediated by individual differences in respondents (Rosenfeld et aI., 1991). There are reasons to believe that this effect extends to Webmediated instruments.…”
Section: Www-mediated Personality Testsmentioning
confidence: 99%
“…In doing so, remote-access Internet-based studies appear to reduce social desirability distortion (Richman, Kiesler, Weisband, & Drasgow, 1999;Tourangeau & Smith, 1996). For example, compared to direct interviews, computer-based assessments have been shown to produce greater disclosure of drinking habits (Locke & Gilbert, 1995), illicit drug use, sexual promiscuity (Tourangeau & Smith, 1996), suicidal ideation (Levine, Ancil, & Roberts, 1989), and lower scores on the Marlowe-Crowne Social Desirability Scale (Martin & Nagao, 1989). Citing research dating back to the 1960s, Richman et al (1999) concluded that "computer instruments reduced social desirability distortion when these instruments were used as a substitute for face-to-face interviews, particularly when the interviews were asking respondents to reveal highly sensitive personal behavior" (p. 771).…”
Section: Social Desirability and Internet-based Researchmentioning
confidence: 99%